Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2528/pierc11100803
|View full text |Cite
|
Sign up to set email alerts
|

Improved Artificial Bee Colony for Design of a Reconfigurable Antenna Array With Discrete Phase Shifters

Abstract: Abstract-Multi-beam antenna arrays have important applications in the field of communications and radar. The reconfigurable design problem is to find the element in a sector pattern main beam with side lobes. The same excitation amplitudes applied to the array with zero-phase should be in a high directivity, low side lobe pencil shaped main beam. This paper presents a new method of designing a reconfigurable antenna with quantized phase excitations using an improved artificial bee colony, called IABC. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Inspired by this algorithm, the control parameter, i.e., modification rate (MR) is used. In order to produce a candidate food position v ij from the current memorized x ij , improved ABC algorithm uses the following expression [30]:…”
Section: Modified Artificial Bee Colony (Mabc) Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by this algorithm, the control parameter, i.e., modification rate (MR) is used. In order to produce a candidate food position v ij from the current memorized x ij , improved ABC algorithm uses the following expression [30]:…”
Section: Modified Artificial Bee Colony (Mabc) Algorithmmentioning
confidence: 99%
“…Despite the simplicity and the superiority of ABC algorithm, recent studies reported that it suffers from a poor exploitation process and a slow convergence rate. To overcome these pitfalls, some research papers have introduced modifications to the classical ABC algorithm in order to improve its performance and tackle more complex realworld problems [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this algorithm, we also use a control parameter, i.e., modification rate (MR). In order to produce a candidate food position v ij from the current memorized x ij , improved ABC algorithm uses the following expression [17]: …”
Section: Modified Artificial Bee Colony (Mabc) Algorithmmentioning
confidence: 99%
“…Despite the simplicity and the superiority of ABC algorithm, recent studies reported that it suffers from a poor exploitation process and a slow convergence rate. To overcome these pitfalls, some research papers have introduced modifications to the classical ABC algorithm in order to improve its performance and tackle more complex real-world problems [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of ABC's generation are Parallel ABC, Smart Flight ABC, Multiple Onlooker ABC, Modified ABC and Improved ABC. According to these developments are known that main advantages are better abilities to get out of optimal results and superior performances for finding solutions [10], [17], [18], [19], [20], [21], [2]. From these works are devoted to the future studies in convergence speeds, searching mechanisms and real applications.…”
Section: Introductionmentioning
confidence: 99%